PENGEMBANGAN POSBINDU LANSIA DI POSBINDU JERUK DESA CIPAYUNG KECAMATAN CIPUTAT KOTA TANGERANG SELATAN PROPINSI BANTEN - Nunuk Nugrohowati; Gatot Soeryo Koesoemo; Kristin Simanjuntak (Jurnal Bakti Masyarakat Indonesia, 2020)
The increasing life expectancy of increasing the number of elderly people in Indonesia can have positive and negative impacts. The need for empowerment and enhancing the role of the community as well as empowering the public and private partnerships, for example, Elderly integrated counseling post (Posbindu) who conducts early detection and monitoring of risk factors for non-communicable diseases in an integrated, routine and periodic manner. The development of the Elderly Posbindu in the village of Cipayung, Ciputat sub-district according to the Guidelines, needs to be developed. The formulation and management of the development of the Elderly Posbindu program in Cipayung village, Ciputat District, South Tangerang City. The incomplete Elderly Posbindu Cadre and the completeness of the Posbindu facilities according to the Ministry of Health's instructions encouraged us to develop the elderly Posbindu in Cipayung village, Ciputa District by comparing with the instructions from the Ministry of Health. After discovering the potentials, problems, and challenges in the development of the Posbindu Elderly in this region, we implemented a plan for the development of the elderly Posbindu Jeruk in the form of meeting the limited posbindu facilities, conducting non-communicable diseases counseling and training cadres in blood sugar level checks. The provision of health service facilities encourages the community to raise awareness of healthy lifestyles, invites the involvement of the elderly community in the health promotion program independently so that they become eager to live a healthy life and life expectancy is increased. Improving the quality of health workers in the context of prevention and increasing counseling in the health sector in the context of handling non-communicable diseases.ABSTRAK:Meningkatnya angka harapan hidup menambah jumlah lansia di Indonesia dapat berdampak positif dan negatif. Perlunya pemberdayaan dan peningkatan peran masyarakat serta pemberdayaan kemitraan pemerintah dan swasta, misalnya Posbindu Lansia yang melakukan kegiatan deteksi dini dan pemantauan faktor risiko Penyakit Tidak Menular secara terpadu, rutin, dan periodik. Masih belum terselenggarakannya Posbindu Lansia di desa Cipayung, kecamatan Ciputat sesuai Petunjuk, perlu dibuat pengembangannya. Terumuskannya dan menata laksana pengembangan program  Posbindu Lansia di desa Cipayung Kecamatan Ciputat Kota Tangerang Selatan. Belum lengkapnya Kader Posbindu Lansia dan kelengkapan fasilitas posbindu sesuai petunjuk kemenkes mendorong kami melakukan pengembangan posbindu lansia di desa Cipayung Kecamatan Ciputa dengan cara membandingkan dengan syarat petunjuk dari Kemenkes.  Setelah ditemukan potensi, permasalahan dan tantangan dalam pengembangan Posbindu Lansia di wilayah ini, kami menerapkan rencana pengembangan posbindu lansia Jeruk berupa pemenuhan fasilitas posbindu yang masih terbatas, mengadakan penyuluhan penyakit tidak menular dan melatih kader dalam pemeriksaan kadar gula darah. Penyediaan sarana pelayanan kesehatan mendorong masyarakat meningkatkan kepedulian pola hidup sehat, mengajak keterlibatan masyarakat lansia pada program sosialisasi kesehatan secara mandiri sehingga kembali bersemangat untuk hidup sehat dan angka harapan hidup menjadi meningkat. Meningkatkan kualitas tenaga kesehatan dalam rangka pencegahan serta peningkatan penyuluhan di bidang kesehatan dalam rangka penanggulangan penyakit tidak menular